Thermodynamics of radiation induced amorphization and thermal annealing of Dy2Sn2O7 pyrochlore. (15th August 2018) - Chung, Cheng-Kai; Lang, Maik; Xu, Hongwu; Navrotsky, Alexandra
Abstract: Thermodynamics and annealing behavior of swift heavy ion amorphized Dy2 Sn2 O7 pyrochlore were studied. Its amorphization enthalpy, defined as the total energetic difference between the irradiation amorphized and undamaged Dy2 Sn2 O7 states, was determined to be 283.6 ± 6.5 kJ/mol by high temperature oxide melt drop solution calorimetry. It has been an enigma that stannate and some other pyrochlores do not follow the general rA /rB −radiation resistance relation seen in most pyrochlore systems. In this work, we use the amorphization enthalpy, which reflects all the complex chemical and structural characteristics, as a more effective parameter to correlate the radiation damage resistance of pyrochlores with their compositions. It successfully explains the superior radiation damage resistance of the stannate pyrochlores compared with titanate pyrochlores. Differential scanning calorimetry (DSC) reveals a strong exothermic event starting at 978 K, which is attributed to long-range recrystallization based on X-ray diffraction (XRD) analysis, similar to the effect previously observed in Dy2 Ti2 O7 . A second pronounced heat event beginning at ∼1148 K, which results from local structural rearrangement, is clearly decoupled from the first event for irradiated Dy2 Sn2 O7 . Both the heat releases measured by DSC on heating to 1023 and 1473 K, and the excess enthalpies of the annealed samples indicate that the recovery to the original, ordered state was not fully achieved up to even 1473 K, despite XRD showing the apparent restoration of crystalline pyrochlore structure. The remaining metastability may be attributed to local disorder in the form of weberite-like short-range domains in the recrystallized material. Intriguingly, the second event for different pyrochlores generally starts at similar temperatures while the onset of the long range recrystallization is compositionally dependent. The amorphization and thermal annealing behavior observed in irradiated Dy2 Sn2 O7 may provide insights into the general mechanisms of radiation damage and recovery of pyrochlores relevant to their nuclear applications. Graphical abstract: Image 1